البحث بإمكانية تصميم الخلائط الإسفلتية باستخدام الإسفلت الرغوي - حنا, رامي; سلطان, بسام; صالح, علي (Latakia University Journal -Engineering Sciences Series, 2019)
A safe and effective road system needs to provide a significantly sustainability roads pavement. According to the lofty principles for the development and modernization process, especially in the exceptional circumstances of our country and the next phase of reconstruction, Services through the development of methods and upgrade it, especially in the transport sector as the most important sector within any country. The traditional asphalt mixtures suffer from low weather resistance and low durability, with average rehabilitation every five years. This study focused on the possibility of manufacturing asphalt mixtures using foam asphalt within study the possibility of manufacturing foamed asphalt, considering the possibility of manufacturing locally. The main objective of this research is to increase the design age of pavement and easily constructed in addition to increase the durability of bituminous mixtures to the effect of external factors and to provide of building costs where the providing by using foamed asphalt has reached to (7-12) %. We could design a small device for the production of foam asphalt (can be developed), the required quantity has been produced for conducting experiments and studying the reality of asphalt mixtures locally. Over all, the final result prove that the use of foam asphalt increases the properties of asphalt mixtures and its main requirements than the normal mixtures and gives indicators to increase the durability of pavement. أدت الحاجة إلى توفير نظام طرق آمن وفعال، لزيادة كبيرة في الطلب على وسائل تزيد من ديمومة الرصف الطرقي، وانطلاقاً من المبادئ السامية الرامية إلى استكمال مسيرة التطوير والتحديث وخصوصا في ظل الظروف الاستثنائية التي يعيشها بلدنا ومرحلة إعادة الأعمار القادمة فيجب أن نولي الاهتمام الكبير لتحسين مستوى الخدمات من خلال تطوير أساليب ترفع من سويتها خصوصا في قطاع النقل باعتباره القطاع الأهم ضمن قطاعات أي بلد. تعاني الخلائط الإسفلتية التقليدية من ضعف في مقاومتها للعوامل الجوية مما يؤثر على ديمومتها حيث تتم إعادة تأهيل الطرق وسطياً كل خمس سنوات. تم التركيز في بحثنا على إمكانية تصنيع خلائط اسفلتية باستخدام الإسفلت الرغوي مع دراسة إمكانية تصنيع الاسفلت الرغوي نفسه محليا وتكمن أهمية البحث في زيادة العمر التصميمي للرصف وسهولة تنفيذ خلائط الإسفلت الرغوي بالإضافة إلى زيادة ديمومة الخلطات البيتومينية ومقاومة العوامل الخارجية وتوفير في كلف الإنشاء حيث بلغ الوفر باستخدام الاسفلت الرغوي ما بين 7-12%. تمكنت من تصنيع جهاز صغير (قابل للتطوير) لإنتاج الإسفلت الرغوي يعطي الكمية اللازمة لإجراء التجارب ودراسة واقع الخلطات الإسفلتية محلياً. توصل البحث إلى أن استخدام الإسفلت الرغوي يزيد من خواص الخلطات الإسفلتية ومتطلباتها الاساسية مقارنة بالخلطات العادية ويعطي مؤشرات لزيادة ديمومة الرصف الطرقي.